Cissus erecta (Vitaceae), a new non-viny herbaceous species from Mt. Popa, Myanmar - Cho, Seong-Hyun; Lee, Jung-Hoon; Kang, Dae-Hyun; Kim, Bo-Yun; Trias-Blasi, Anna; Htwe, Khin Myo; Kim, Young-Dong (Phytotaxa, 2016)
Cissus erecta, a new endemic species of Vitaceae from Myanmar, is described and illustrated. The species is similar to C. aubertiana in habit, but it is readily distinguished by its less deeply lobed leaves with serrate margins, persistent stipules, and larger berries. This species is also similar to C. woodrowii in leaf shape, but it is distinguished by having herbaceous habit, leaves with serrate margin, greenish and persistent stipules, compound umbel, and larger globose berries.